MINAT BELI KONSUMEN DALAM PENGARUHNYA TERHADAP KUALITAS PRODUK DAN HARGA JUAL DALAM PRESPEKTIF EKONOMI SYARIAH - Yumsinah, Siti (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2023)
The tight competition in today's business world requires every shop owner to be active in attracting and retaining customers. The problems that arise in the Mandiri Electronic Shop Kadubera are more directedat providing quality goods and setting the selling price. The problem formulations of this study are: 1. Is there an effect of product quality and price on consumer buying interest in the Kadubera electronic independent shop? 2. How much influence does product quality and price have on consumer buying interest in Kadubera electronic independent stores?. The objectives of this study are: 1. To find out whether there is an effect of product quality and price on consumer buying interest in kadubera electronic independent stores, 2. To find out how much influence product quality and price have on consumer buying interest in kadubera electronic independent stores. The method used in this research is a quantitative approach, This study concluded that the Fcount for the independent variables (Product Quality and Price) was 37.911 with a significant level of 0.000. While the Ftable value at α = 0.05 is 3.08, then the Product Quality and Price variables simultaneously have a positive and significant effect on Consumer Purchase Interest (Y) at the Mandiri Elektronik Kadubera Store. Furthermore, the results of the coefficient of determination show that R2 is 41.3% independent variables (Product Quality and Price) explaining the dependent variable (Consumer Purchase Interest) and 58.7% influenced by other variables outside this study.